RANCANG BANGUN WEBSITE INVENTARIS BERBASIS QR CODE UNTUK PENDATAAN BARANG DI POLITEKNIK NEGERI SAMARINDA - Alif Febriantino Suyitno; M. Farman Andrijasa; M. Zainul Rohman (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The data collection and borrowing process of goods at the Department of Information Technology, Samarinda State Polytechnic, which is still carried out manually, results in slow services and is prone to errors in data recording. This research aims to design and build a QR Code-based inventory website to overcome the problems at the Department of Information Technology. The system was built and developed using the PHP programming language, the Laravel framework, a MySQL database, and utilizes Filament as an admin panel, following the Waterfall model consisting of analysis, design, implementation, testing, and maintenance stages. The main features of this system include item data management, borrowing, returns, procurement, PDF report printing, low-stock notifications, and QR Code integration to accelerate item identification. Functional testing using the Blackbox Testing method across all website function scenarios shows that the system operates as required and achieves a 100% success rate. The research results show that the system is proven to improve work efficiency, minimize recording errors in data collection, and support transparency in asset management within the department environment.